Estimation of Genetic Parameters for Litter Traits in Taiwan Duroc, Landrace, and Yorkshire Pigs - P. Silalahi; Y. C. Chen (Faculty of Animal Science, Bogor Agricultural University, 2023)
Selection for reproductive components in various pig populations in the world has been successfully performed. This study aimed to estimate the genetic parameters and genetic trends of reproductive traits of Taiwan Duroc, Landrace, and Yorkshire pigs. Data were extracted from the Taiwan Swine Registry Database from 2009 to June 2018. The number of farrowing records used in this study was 6,504, 6,398, and 2,178 for Duroc, Landrace, and Yorkshire, respectively. Litter traits measured were the number of piglets born alive (NBA), number of piglets at 21 days of age (N21D), litter weight at birth (LWB), and litter weight at 21 days of age (LW21D). Variances estimates obtained from univariate analysis with a repeatability model were used to estimate heritability and repeatability. Heritability estimates were 0.058±0.017, 0.037±0.014, and 0.101±0.032 for NBA; 0.086±0.018, 0.102±0.019, and 0.151±0.035 for N21D; 0.036±0.011, 0.111±0.021, and 0.330±0.05 for LWB; 0.119±0.020, 0.168±0.023, and 0.237±0.045 for LW21D in the Duroc, Landrace, and Yorkshire breeds, respectively. The genetic trends of NBA were 0.005 piglets/year for the Duroc and 0.002/piglets for the Landrace. In Yorkshire, conversely, there was no significant genetic improvement of NBA, but there was a 0.011 kg/year improvement of LWB. Among all genetic trends, it was shown that genetic gain in Taiwan pig populations was very low. In addition, it also suggested that genomic selection could be used in the Taiwan pig breeding program to push the rate of genetic gain.